PROMOTING SMALL AND MEDIUM ENTERPRISES IN THE NIGERIAN OIL AND GAS INDUSTRY - Aigboduwa, Joseph E.; Oisamoje, Michael D. (European Scientific Journal, ESJ, 2013)
Small and medium scale enterprises (SMEs) are generally acknowledged as having huge potentials for employment generation and wealth creation in any economy. Hence interest in their development continues to be in the forefront of policy debates. In Nigeria however, the sector remains relatively small in terms of its contribution to GDP or to gainful employment. Though the Nigerian Oil and Gas Industry has played pivotal role in the economic development of the country since independence, with over 95% of total export revenue currently accruing from this sector, the participation of SMEs in the sector has been largely insignificant. However, the enactment of the Nigerian Content Development Act 2010 provides a number of opportunities for Nigerians to participate in the oil and gas sector. This paper examines the historical trend in the development of SMEs in Nigeria and identifies the several opportunities and competitive advantages now exclusively reserved for Nigerian companies under the Nigerian Content Act. The access to funding for development of the capital base of SMEs is emphasised, and it is suggested that the Act would offer a turning point in the realisation of all the policy trusts formulated for growing SMEs in Nigeria in the future.